La loma de los empalados y la tierra de nadie : frontera y guerra en la Provincia de Antioquia, 1540-1550 (2013)
ABSTRACT: This paper studies certain forms of violence which occurred during the conquest of Antioquia between 1540 and 1550. As this province was a border area, both because of the aboriginal resistance and because of the confrontation between the governorates of Cartagena and Popayan, war and punishment against indigenous peoples was gruesome, even for the context of the Conquest. The aim of the paper is not to study the uniqueness of Antioquia, but to show that the border war was an imperial problem and that it relaxed morals allowing a punitive system foreign to civilized confrontation but valid in peripheral areas.